Relationship between advanced footwear technology longitudinal bending stiffness and energy cost of running - Rodrigo-Carranza, V.; Hoogkamer, W.; González-Ravé, J. M.; González-Mohíno, F. (Scandinavian Journal of Medicine & Science in Sports, 2024)
Introduction/Purpose Shoe longitudinal bending stiffness (LBS) is often considered to influence running economy (RE) and thus, running performance. However, previous results are mixed and LBS levels have not been studied in advanced footwear technology (AFT). The purpose of this study was to evaluate the effects of increased LBS from curved carbon fiber plates embedded within an AFT midsole compared to a traditional running shoe on RE and spatiotemporal parameters.